Study of the Thermal Durability of Refractory Mortar Prepared from Local Clay Mixed with Different Percentage of Silica - Kadhum, Mustafa; Jaffer, H. (Iraqi Journal of Science, 2024)
Refractory mortar was prepared from the mixing of locally fire clay with different percentage of silica powder (30,40,50,60)wt% by using Pyrometric Cone Equivalent PCE . According to the U.S. Standard ASTM C24, the samples were prepared by using Hand – molding method and dried at temperature 110⁰C and finally firing at different temperature (1000,1100,1200,1300)⁰C according to burning program to study the effect of temperatures for these specimens on the thermal durability .It was shown that the increasing in the percentage of silica content increased the durability of heat specimens, and the best degree of burn was 1300°C.